Enhancing Public Knowledge of Musculoskeletal Disorders across 12 Subdistricts of Tasikmalaya - Yedy Purwandi Sukmawan; Anisa Pebiansyah; Ilham Alifiar (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2026)
Background: Musculoskeletal disorders such as hyperuricemia, osteoarthritis, osteoporosis, and rheumatoid arthritis are increase in prevalence, including in Indonesia, yet public understanding of these conditions remains insufficient.Aims: This study aimed to evaluate the effectiveness of pharmacist-led health promotion initiatives in enhancing public knowledge regarding the etiology, symptoms, and pharmacological treatment of these four musculoskeletal conditions.Methods: Utilizing a pre-experimental One-group pretest-posttest design, the research was conducted across twelve subdistricts in Tasikmalaya City and Tasikmalaya Regency. Participants were selected through total sampling, and data were collected using structured questionnaires administered before and after interactive educational sessions. The key success indicators were a post-test score ≥80 and/or a statistically significant difference (p < 0.05).Results: The program engaged 416 participants across four interventions: hyperuricemia/gout (n=140), osteoarthritis (n=110), osteoporosis (n=101), and rheumatoid arthritis (n=65), consisting predominantly of female participants, particularly pre-elderly and elderly housewives. Conclusion: The health education program significantly improved community knowledge concerning musculoskeletal health and medications, which is anticipated to aid in reducing disease prevalence and improving the quality of life for patients in the region.